Patient participation in multidisciplinary tumor conferences: Providers' perceptions of patients' need satisfaction and emotional experiences. Issue 8 (1st June 2020) - Diekmann, Annika; Heuser, Christian; Schellenberger, Barbara; Bohmeier, Barbara; Holmberg, Christine; Ansmann, Lena; Ernstmann, Nicole
Abstract: Objective: In some breast and gynecological cancer centers in Germany, patients participate in multidisciplinary tumor conferences (MTCs) during the discussion of their own case. The aim of this study was to explore providers' perceptions concerning patients' emotional experiences during participation in an MTC by comparing the perspectives of providers with and without experience with patient participation. Methods: In this study, semi‐structured interviews with n = 30 providers in n = 6 breast and gynecological cancer centers in North Rhine‐Westphalia, Germany, were conducted. One half of the providers had no experience and the other half had experience with patient participation in MTCs. The interviews were audiotaped and transcribed, and content analysis was performed. Results: The results of this study show a mixed picture of met, unmet and disappointed needs of patients and their emotional reactions, which mainly overlap between both provider groups. Our results show that both provider groups report positive and negative experiences or expectations. Conclusion: The mixed results regarding expected and perceived patient experiences from the providers' perspective suggest that patient participation in MTCs may not be exclusively of benefit. Further research on advantages and disadvantages for patients and on feasibility from the providers' perspective is necessary and will be conducted within the PINTU project.